Platelet gene therapy induces robust immune tolerance even in a primed model via peripheral clonal deletion of antigen-specific T cells - Jing Li; Juan Chen; Jocelyn A. Schroeder; Jianda Hu; Calvin B. Williams; Qizhen Shi (Elsevier, 2021)
While platelet-specific gene therapy is effective in inducing immune tolerance to a targeted protein, how the reactivity of pre-existing immunity affects the efficacy, and whether CD8 T cells were involved in tolerization, is unclear. In this study, ovalbumin (OVA) was used as a surrogate protein. Platelet-OVA expression was introduced by 2bOVA lentivirus transduction of Sca-1+ cells from either wild-type (WT)/CD45.2 or OT-II/CD45.2 donors followed by transplantation into OVA-primed WT/CD45.1 recipients preconditioned with 6.6 Gy of irradiation. Sustained platelet-OVA expression was achieved in >85% of OVA-primed recipients but abolished in animals with high-reactive pre-existing immunity. As confirmed by OVA rechallenge and skin graft transplantation, immune tolerance was achieved in 2bOVA-transduced recipients. We found that there is a negative correlation between platelet-OVA expression and the percentage of OVA-specific CD4 T cells and a positive correlation with the OVA-specific regulatory T (Treg) cells. Using the OT-I/WT model, we showed that antigen-specific CD8 T cells were partially deleted in recipients after platelet-targeted gene transfer. Taken together, our studies demonstrate that robust antigen-specific immune tolerance can be achieved through platelet-specific gene therapy via peripheral clonal deletion of antigen-specific CD4 and CD8 T effector cells and induction of antigen-specific Treg cells. There is an antagonistic dynamic process between immune responses and immune tolerance after platelet-targeted gene therapy.